2014
DOI: 10.1088/1367-2630/16/12/123029
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order interference and single-system postulates characterizing quantum theory

Abstract: We present a new characterization of quantum theory in terms of simple physical principles that is different from previous ones in two important respects: first, it only refers to properties of single systems without any assumptions on the composition of many systems; and second, it is closer to experiment by having absence of higher-order interference as a postulate, which is currently the subject of experimental investigation. We give three postulates-no higher-order interference, classical decomposability o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
319
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(325 citation statements)
references
References 85 publications
(162 reference statements)
6
319
0
Order By: Relevance
“…However, taking into account the earlier successful predictions of the E principle [18][19][20][21][22][23] and the evidences of failure of other approaches [8][9][10], the result presented here promotes the E principle as the best option for understanding the limits of quantum contextual and nonlocal correlations. This apparent fundamental role of the E principle in QT is also supported by some recent results aiming to understand QT from fundamental physical principles [15,27,28].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…However, taking into account the earlier successful predictions of the E principle [18][19][20][21][22][23] and the evidences of failure of other approaches [8][9][10], the result presented here promotes the E principle as the best option for understanding the limits of quantum contextual and nonlocal correlations. This apparent fundamental role of the E principle in QT is also supported by some recent results aiming to understand QT from fundamental physical principles [15,27,28].…”
supporting
confidence: 62%
“…Later Specker conjectured that the E principle could be the fundamental principle of QT [26]. Recent works have shown that the E principle is implied by physical principles of a very different nature [15,27,28].…”
mentioning
confidence: 99%
“…O is free to restrict his description of Q by erasing any questions from it that are redundant through equivalence. 9 As a result, every question vector q, if physically permitted at all, will correspond to a unique Q ∈ Q.…”
Section: How To Compute Probabilitiesmentioning
confidence: 99%
“…Among them are violation of the Bell [2,3] and more generally Clauser-Horne-Shimony-Holt inequalities [4], the 'no-signaling' principle [5] and, its generalization, 'information causality' [6], interference effects in mixtures [7], absence of third and higher order interference [8,9], a limit on the information content carried by systems [10][11][12][13][14][15][16][17][18][19][20][21][22] and others. However, all of these attributes yield incomplete characterizations, being shared by other probabilistic theories some of which admit unphysical correlation structures, as well as exotic information communication and processing tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation